High-accuracy incident signal reconstruction for in-situ ultrasonic measurement of oil film thickness. (July 2021) - Dou, Pan; Jia, Yaping; Wu, Tonghai; Peng, Zhongxiao; Yu, Min; Reddyhoff, Tom
Highlights: The relationships of the reflected signal and the incident signal are clarified. The spectrum of the incident signal is obtained from the reflected signals. A reconstruction algorithm of the incident signal is proposed. Abstract: The oil film thickness in an oil-lubricated tribo-pair can be measured using reflected ultrasonic waves and various transformation models. Conventionally, this approach requires the incident signal to be calibrated using off-line methods prior to testing, and this limits the on-line measurement of oil film thickness in sliding components such as journal bearings. To enable on-line calibration, we propose a method of reconstructing the incident signal from the easily obtained reflected signal. This involves analyzing the amplitude and phase spectrum of the reflection coefficient to reconstruct the incident signal. More specifically, the following main findings of the amplitude and phase of reflection coefficient at the resonance frequency are reported. 1) There is a zero-crossing at the resonance frequency, and therefore the phases of the incident and reflected signal are the same. 2) If part of the reflected signal is included for calculation, the frequency of the extreme point in the amplitude spectrum of the reflected signal is equal to the resonance frequency only when the extreme point phenomenon occurs at the center frequency of the transducer. At other positions, the frequency of the minimum amplitude in the amplitude spectrum of the reflected signal is not equal to the resonance frequency. Utilizing these relationships, the phase and amplitude of the incident signal can be accurately reconstructed by following the proposed method, provided the thickness of the oil film between the tribo-pairs can be widely ranged to cover both the blind and the resonance zones. Correspondingly, a practical schedule for the on-line reconstruction of the incident signal is proposed, which includes an operation to adjust the oil film thickness within the blind and the resonance zone. This method is validated on a test rig by comparing it with the traditional off-line methods.